First principles calculations and experiments for Cu-Mg/Li hydrides negative electrodes - M. H. Braga (2013)
We have studied CuLi0.08Mg1.92 and determined that the compound reacts with hydrogen to form CuLi0.08Mg 1.92H5 [1]. Additionally, we have proposed the compound as a negative electrode material which is the main purpose of the present study. Moreover, we have observed that the latter compound acts as a catalyst in the formation of MgH2, LiH, TiH2 [2] and hydrogen desorption. In this work, first principles and phonon calculations were performed in order to establish the reactions occurring at the negative electrode of a Li conversion battery in presence of CuLi0.08Mg1.92H 5 and (Li) - solid solution of Mg in Li - Approximately Li 2Mg3. We have calculated the minimum theoretical specific capacity to be 1156 mAh/g (for an anode with 100% of CuLi0.08Mg 1.92H5) and the Eeq = 0.81 V (vs. Li+/Li) at 298 K. Furthermore, we have determined all the reactions occurring in the referred system and its sequence using Inelastic Incoherent Neutron Scattering (TINS) and X-Ray Diffraction (XRD). (c) 2013 Materials Research Society.